Measuring Passage Contribution in ESL Reading Comprehension - Perkins, Kyle; Jones, Barbara (TESOL quarterly, 1985)
Reports on an analysis of two administrations of two reading tests--the first time without the reading passages and the second time with the passages--in order to determine the extent to which questions can be answered without reading the texts on which they are based. (SED)